2001
DOI: 10.1002/1096-9896(2000)9999:9999<::aid-path792>3.3.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

The effect of myocardial bridging of the coronary artery on vasoactive agents and atherosclerosis localization

Abstract: The relationship between alterations in the immunohistochemical expression of three vasoactive agents [endothelial nitric oxide synthase (eNOS), endothelin-1 (ET-1), and angiotensin-converting enzyme (ACE)] and the occurrence human atherosclerosis was investigated in relation to the myocardial bridge (MB) of the left anterior descending coronary artery (LAD), an anatomical site that experiences increased shear stress. Five millimetre cross-sections of LADs with MB from 22 autopsied cases were taken from the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 0 publications
3
42
1
3
Order By: Relevance
“…46 Furthermore, an immunohistochemical study has shown that the expression of endothelial nitric oxide synthase is suppressed beneath MB. 47 These findings support our hypothesis that vascular dysfunction occurs in MB segments.…”
Section: Possible Mechanisms Accounting For the Increased Frequency Osupporting
confidence: 87%
“…46 Furthermore, an immunohistochemical study has shown that the expression of endothelial nitric oxide synthase is suppressed beneath MB. 47 These findings support our hypothesis that vascular dysfunction occurs in MB segments.…”
Section: Possible Mechanisms Accounting For the Increased Frequency Osupporting
confidence: 87%
“…Several pathology studies have been performed assessing the extent of atherosclerosis, particularly within the bridge, in patients with MB [34]. Altogether, the data suggest that MB is associated with the decreased development of atherosclerosis under and proximal to the tunnelled artery, although it is unclear whether this is an independent factor [35]. It seems that MB located within 5 cm from the left coronary ostium may prevent atherosclerosis in the proximal part of LAD [36].…”
Section: Myocardial Bridging and Coronary Lesionsmentioning
confidence: 99%
“…In 2001, Masuda et al [13] investigated the relationship between the expression of main vasoactive agents such as endothelin-1 (ET-1), the angiotensin converting enzyme (ACE) and endothelial nitric oxide synthase (eNOS), with its location in relation to myocardial bridge and the degree of involvement by arteriosclerosis. They found that in the intramyocardial portion of the left anterior descending artery there was no histopathological sign indicating the beginning of arteriosclerosis in the intima and that the arteriosclerosis rate is significantly smaller in the myocardial bridge portion in relation to the proximal and distal segments of the bridge.…”
Section: Expression Of Vasoactive Agentsmentioning
confidence: 99%
“…They established a significant association between both the differential expression of vasoactive agents along the anterior descending coronary artery with less expression in the myocardial bridge as an association between decreased expression of vasoactive agents with lower arteriosclerosis rates. It was demonstrated that the expression of vasoactive agents is related to an altered hemodynamic stress on the vascular wall, suggesting that the decrease of shear stress, beyond interfering with the lipid transfer phase to the vascular wall in arteriogenesis, also works to reduce the expression of vasoactive agents (Figure 3) [13].…”
Section: Expression Of Vasoactive Agentsmentioning
confidence: 99%